Is resection of pancreatic adenocarcinoma with synchronous hepatic metastasis justified? A review of current literature. Issue 12 (31st August 2016) - Antoniou, Efstathios; Margonis, Georgios A.; Sasaki, Kazunari; Andreatos, Nikolaos; Polychronidis, Georgios; Pawlik, Timothy M.; Pikoulis, Emmanouil
Abstract : Background: Pancreatic ductal adenocarcinoma (PDAC) is an extremely lethal neoplastic process, largely due to the presence of disseminated disease at presentation. As such, evidence‐based management of metastatic disease is integral to patient care in such circumstances. This review aimed to summarize the current state of knowledge regarding the potential effectiveness of liver metastasectomy in the setting of PDAC. Methods: A structured review of the literature was performed from April to May 2016, using the PubMed database. Relevant original research articles and systematic reviews/meta‐analyses published between 1990 and 2015 were considered eligible. The primary endpoint was overall survival in patients undergoing resection for PDAC and liver metastasectomy. Studies reporting on fewer than 10 patients were excluded. Results: Ultimately, eight studies met our inclusion criteria. Their results suggest that hepatic metastasectomy for PDAC is a safe procedure, with a potential survival benefit for carefully selected patients, particularly those with metachronous metastases. Nonetheless, small sample sizes and inconsistent use of appropriate controls preclude generalization of these findings. Conclusion: Multi‐institutional prospective studies are required to fully delineate the potential therapeutic utility and operative indications of liver metastasectomy in the setting of modern interdisciplinary management of PDAC.